2022
DOI: 10.1177/21925682221110828
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Anesthetics and Postoperative Delirium in Elderly Patients Undergoing Spine Surgery: Propofol Versus Sevoflurane

Abstract: Study designs Retrospective Observational Study Objectives: To compare the incidence of POD after propofol- and sevoflurane-based anesthesia in elderly patients undergoing spine surgery. Methods In this study, the medical records of elderly patients ≥ 65 years of age who underwent spine surgery under total intravenous anesthesia with propofol or inhalational anesthesia with sevoflurane were reviewed. The primary outcome was the incidence of POD after propofol- and sevoflurane-based anesthesia. Secondary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Due to the pharmacokinetic properties of propofol the recovery times, particularly after short procedures, were good and it could be used as a replacement of VA. Furthermore, studies show less risk to develop postoperative delirium when anesthesia is done using propofol than with VA. [1][2][3] This is an advantage in an aver aging patient population and in a costly hospital environment where any additional hour or day of hospitalization needs to be avoided. In Chang et al's 3 study recent study from 2022, the risk of postoperative delirium in elderly patients undergoing spine surgery was increased 3-fold with sevoflurane anesthesia than with propofol anesthesia.…”
Section: Pro Positionmentioning
confidence: 99%
“…Due to the pharmacokinetic properties of propofol the recovery times, particularly after short procedures, were good and it could be used as a replacement of VA. Furthermore, studies show less risk to develop postoperative delirium when anesthesia is done using propofol than with VA. [1][2][3] This is an advantage in an aver aging patient population and in a costly hospital environment where any additional hour or day of hospitalization needs to be avoided. In Chang et al's 3 study recent study from 2022, the risk of postoperative delirium in elderly patients undergoing spine surgery was increased 3-fold with sevoflurane anesthesia than with propofol anesthesia.…”
Section: Pro Positionmentioning
confidence: 99%
“…In a multicenter randomized controlled trial designed to study the incidence of postoperative delirium in two groups of patients assigned to light or deep anesthesia guided by bispectral index (BIS) monitoring, targeting light anesthesia was found to reduce the risk of POCD at 1 year (9% vs. 20% reduction based on an Abbreviated Mental Test score ≤ 6, P < 0.001) [16]. To date, however, studies have been equivocal, resulting in a lack of convincing evidence of any difference in the incidence of POCD between propo-fol-TIVA and inhalational anesthesia [17][18][19][20][21]. Nevertheless, current guidelines Guidelines from the Association of Anaesthetists and the Society for Intravenous Anaesthesia recommend the use of processed electroencephalogram (pEEG) monitoring when a neuromuscular blocking drug is used with TIVA [22], which may be beneficial for avoiding excessive anesthetic depth.…”
Section: Postoperative Delirium and Confusionmentioning
confidence: 99%
“…Our previous studies confirmed this view: propofol (20 mg•kg −1 •h −1 , 6 h) inhibited oxidative stress by regulating the expression of bivalent metal transporter 1. 22 Although propofol has been reported to lessen the incidence of delirium and postoperative cognitive dysfunction, 23,24 its effect on SD-induced cognitive deficits has not been elucidated. Therefore, the present study aimed to investigate the role of propofol in inhibiting microglia hyperactivation, reducing inflammatory levels, and thereby facilitating sleep disorders and cognitive impairment caused by acute SD.…”
Section: Introductionmentioning
confidence: 99%